2020
DOI: 10.1080/17477778.2020.1781556
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the battery price and the car-mix in key electro-mobility markets via model coupling

Abstract: This paper describes the modelling process of soft-linking two system dynamics models of the automotive ecosystem: the Powertrain Technology Transition Market Agent model and the Transport, Energy, Economics, Environment model. The objective of this work is to explore future battery electric and plug-in hybrid electric powertrain deployment in key electromobility markets: China, European Union, India, Japan, Norway and the United States. In the "Alternative" scenario, a combined stock of almost 130 million ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…PHEV production/R&D (automation) FCA (Stellantis) years, two previous review exercises reported by one of the authors are highlighted in [9], where system dynamics (SD) was identified as a prominent method to investigate the uptake of electric cars; in [10], a more in-depth review of a selection of SD models was performed. In comparison to earlier work (e.g., [11,12]), the current study extends previous modelling efforts by modelling balance sheets and assuring the stock-flow consistency (SFC) conditions, meaning an approach in which "the stocks and flows of both real and financial variables must be fully integrated, along with an explicit consideration of their dynamics" (Lavoie in [13]) (p. vii).…”
Section: Introduction 1backgroundmentioning
confidence: 85%
“…PHEV production/R&D (automation) FCA (Stellantis) years, two previous review exercises reported by one of the authors are highlighted in [9], where system dynamics (SD) was identified as a prominent method to investigate the uptake of electric cars; in [10], a more in-depth review of a selection of SD models was performed. In comparison to earlier work (e.g., [11,12]), the current study extends previous modelling efforts by modelling balance sheets and assuring the stock-flow consistency (SFC) conditions, meaning an approach in which "the stocks and flows of both real and financial variables must be fully integrated, along with an explicit consideration of their dynamics" (Lavoie in [13]) (p. vii).…”
Section: Introduction 1backgroundmentioning
confidence: 85%
“…Various policy initiatives, such as the establishment of energy communities, are fostering the development and ongoing adoption of this technology to meet European climate objectives. Anticipated reductions in vehicle and technology costs in the future hold the potential for significant advancements in this field [153][154][155][156][157][158][159][160].…”
Section: Vehicle To Home (V2h)mentioning
confidence: 99%
“…Struben's research has measured the willingness to consider the type of powertrain experiencing a technological transition from ICE to a powertrain with alternative fuels (Struben and Sterman 2008). Other studies build on Struben's research to forecast the market using various methods from dynamic systems, Markov models, and mixedlogit models (Deuten et al 2020;Gomez Vilchez et al 2013;Gomez Vilchez and Thiel 2020;Harrison et al 2016Harrison et al , 2018Jones et al 2013;Pasaoglu et al 2016). In addition, there are studies discussing policies for both electric vehicles, This article is composed of the initial section, namely an introduction related to the topic of technological transition market growth, especially electric motorbikes; the second section is a methodology related to the flow of systematic literature review; the third section is a statistical presentation of the results of articles obtained from the database which are then analyzed based on publication year, journal source, keywords (co-occurrence), author, and article topic, the last section describes the output obtained from this systematic literature review.…”
Section: Introductionmentioning
confidence: 99%